2011
DOI: 10.5194/acp-11-7355-2011
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol modelling in Europe with a focus on Switzerland during summer and winter episodes

Abstract: This paper describes aerosol modelling in Europe with a focus on Switzerland during summer and winter periods. We modelled PM<sub>2.5</sub> (particles smaller than 2.5 μm in aerodynamic diameter) for one summer and two winter periods in years 2006 and 2007 using the CAMx air quality model. The meteorological fields were obtained from MM5 simulations. The modelled wind speeds during some low-wind periods, however, had to be calibrated with measurements to use realistic input for the air quality mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 34 publications
10
83
1
Order By: Relevance
“…As indicated in Table 3, all MFBs and MFEs for p-NH + 4 meet the acceptable model performance criteria (MFE ≤ 75 % and −60 % < MFB < 60 %) suggested by Boylan and Russell (2006). All of the values are also comparable to values reported by other studies (Aksoyoglu et al, 2011;Appel et al, 2008;Tesche et al, 2006), indicating satisfactory performance of the model in simulating p-NH + 4 . Ratio-of-the-means (ROM) values presented in Table 3 indicate that the model predicted means of p-NH 4 measurements very well, with a 2 % to 8 % over-prediction.…”
Section: P-nhsupporting
confidence: 75%
“…As indicated in Table 3, all MFBs and MFEs for p-NH + 4 meet the acceptable model performance criteria (MFE ≤ 75 % and −60 % < MFB < 60 %) suggested by Boylan and Russell (2006). All of the values are also comparable to values reported by other studies (Aksoyoglu et al, 2011;Appel et al, 2008;Tesche et al, 2006), indicating satisfactory performance of the model in simulating p-NH + 4 . Ratio-of-the-means (ROM) values presented in Table 3 indicate that the model predicted means of p-NH 4 measurements very well, with a 2 % to 8 % over-prediction.…”
Section: P-nhsupporting
confidence: 75%
“…Several regional ACTM studies have also reported an underestimation of total OA (Simpson et al, 2007;Murphy and Pandis, 2009;Hodzic et al, 2010;Aksoyoglu et al, 2011;Jathar et al, 2011;Bergström et al, 2012;Koo et al, 2014) and SOA (Hodzic et al, 2010;Shrivastava et al, 2011;Zhang et al, 2013;Fountoukis et al, 2014), with normalized mean biases (NMBs) often in the range of −30 to −50 %. In some cases, this underestimation has been shown to be due to problems with the underlying emission inventories, particularly for domestic wood burning in wintertime (Simpson et al, 2007;Denier van der Gon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…More recent models have included reversibility (Roldin et al, 2014;Trump and Donahue, 2014), which is needed to reproduce perturbations of freshly formed SOA such as changes induced by isothermal dilution, thermal degradation, and/or aging. Regional air quality models show that oligomerization has the potential to significantly increase the SOA mass concentration (Aksoyoglu et al, 2011;Lemaire et al, 2016), and accurately representing this chemistry in these models is perhaps the greatest uncertainty for predicting SOA formation (Shrivastava et al, 2016).…”
Section: Introductionmentioning
confidence: 99%